(untitled) (Plant Tissue Culture and Biotechnology, 2014)
For rapid multiplication and genetic manipulation of African violets (Saintpaulia ionantha Wendl.) was aimed at developing a rapid and efficient regeneration and adaptation system from leaf explants. Using RM medium supplemented with different combinations of growth regulators, we developed a highly efficient and time-saving in vitro regeneration protocol. The developed system was also successfully applied for plant regeneration from petiole and internode explants of several Saintpaulia cultivars at a high efficiency. Regeneration occurred through both somatic embryogenesis and shoot organogenesis at a high frequency. Also, we developed a rapid root formation protocol followed by their efficient adaptation for in vitro regenerated plantlets. Plant Tissue Cult. & Biotech. 24(1): 37-45, 2014 (June) D. O. I. http://dx.doi.org/10.3329/ptcb.v24i1.19194